Leadership dilemmas of women in senior management positions (support) in higher education: strategy, struggles and survival: a case study at the University of Witwatersrand (Wits) - Abrahams, Lamese (My University, 2017)
The purpose of this study was to obtain a deeper understanding of what it takes for women to succeed in senior management positions (support) in higher education institutions. The findings not only offer a wealth of strategies for career success and for overcoming professional and personal challenges, but also sheds new light on critical factors that affect women’s experiences at work. This qualitative study was based primarily on confidential interviews with four senior female participants and two senior male participants. Before assuming their current posts, they worked in a variety of leadership capacities ranging from department head to executive positions at Wits. All interviews were transcribed verbatim, analysed and compared for salient themes. Six major themes emerged from this research: effective leadership strategies; tests and trials; maintaining focus and political savvy; numbers matter; gender as a two-edged sword; and competing as a woman. The results revealed that to succeed as an executive in a higher education institution, women must constantly overachieve, maintain good relationships with others, hold onto personal and institutional values to do the right things, expand themselves constantly, and utilize strong mentors’ assistance. When faced with implicit and explicit challenges such as unequal treatment, gender bias, resistance, political joggling, or personal struggles, they rely on private confrontation, emotional intelligence, and tenacity, as well as all possible support and resources to survive and thrive. The literature reviewed demonstrated that these factors are not exclusively experienced in the higher education sector and thus the results could be of interest to both the private and public sector. Given the importance of gender diversity in our modern society, the researcher believes that this study is critical in assisting Wits to understand why there are still so few females in senior management positions. It is hoped that the research will assist Wits to make changes to support the development and progression of more women into senior leadership roles in the future. iv Finally, although it is beyond the scope of this study to do more than speculate about the implications of the literature for leadership and gender issues, the relative lack of progress made during the last 40 years in terms of women occupying senior management positions, suggest that the discourse around these findings particularly at Wits needs to be more robust, redefined and more rigorous on the view to attracting, developing, retaining and promoting women into senior management positions.
A research report submitted to the Faculty of Humanities in partial fulfillment of the Degree of Master of Education, University of the Witwatersrand, Johannesburg, 2017
Keywords: Educational leadership--South Africa; Leadership; Women in education